Prevalence of overweight and obesity, body image perception and weight control practices among college going adolescent girls in Mysore District, Karnataka - N., Srinivas; M. R., Ravi; B., Prashantha; B., Prakash (International Journal Of Community Medicine And Public Health, 2017)
Background: The World Health Organization has described obesity as one of today’s most neglected public health problems. Body image is a psychosocial dimension of body size that encompasses both perceptual and attitudinal factors and has been associated with eating disorders. Adolescents are becoming over conscious of their body image. Body weight perception refers to the personal evaluation of one’s weight irrespective of actual BMI. The objectives of the study was to assess the prevalence of overweight and obesity, body image perception and weight control practices among college going adolescents girls and to determine differences between existing BMI and body image perception among college going adolescents girls. Methods: A cross-sectional study was conducted among college going adolescents girls in Mysore district, two colleges were randomly selected and 661 study participants were participated in the study. Data was collected through a self-administered pre tested structured questionnaire and height and weight were measured using standard tools to calculate body mass index. Results: Among the study percipients prevalence of overweight and obesity was found to be 36 (5.4%) and 43 (6.5%) respectively, whereas 70 (10.6) feel they are obese and 386 (59.2%) were ever practiced weight control methods. Body image perception and actual weight were found to statistically significant. Conclusions: Perception about body image as obese was higher among adolescents. Hence adolescents should be given education regarding body mass index and expected BMI for their age and about appropriate dietary practices.